Effect of volatile compounds on the quality of Japanese fermented soy sauce. (August 2019) - Wang, Shuo; Tamura, Takehiro; Kyouno, Nobuyuki; Liu, Xiaofang; Zhang, Han; Akiyama, Yoshinobu; Chen, Jie Yu
Abstract: To understand the effects of volatile compounds on the evaluation of soy sauces so their quality could be classified, samples collected over 3 consecutive years from 2015 to 2017 were evaluated then ranked. The volatile compounds of these evaluated samples were directly extracted by headspace analysis to reduce technical interference and to identify the most common compounds in soy sauce. Sixty-four volatile compounds were identified in the evaluated soy sauces, of which 35 were found in all samples. The correlation coefficients between the levels of volatile compounds detected and the sensory rankings of the evaluated soy sauces were calculated. This enabled those volatile compounds having a greater measure of influence, both negatively and positively, on the quality of the soy sauce to be identified. It was noteworthy that the quality of Japanese fermented soy sauces was negatively correlated with their levels of 4-ethyl-2methoxyphenol and pyrazines. Highlights: Volatile compounds were correlated directly to the sensory evaluation. 19 compounds were found to be positively correlated with the quality increased. 25 compounds showed a negative correlation to sensory quality of soy sauce. The obtained results provide additional data for flavor optimization of soy sauce.